2018
DOI: 10.1096/fj.201701111rr
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine actions of prolactin contribute to the regulation of lactotroph function in vivo

Abstract: Prolactin (PRL), whose principal role is regulation of lactation, is mainly synthesized and secreted by lactotroph anterior pituitary cells. Its signaling is exerted via a transmembrane PRL receptor (PRLR) expressed in a wide variety of tissues, including the anterior pituitary. Dopamine, which is secreted by tuberoinfundibular hypothalamic neurons, is the major inhibitory regulator of prolactin secretion. Although PRL is well established to stimulate hypothalamic dopamine secretion, thereby exerting a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…For example, deletion of Prlr in different subtypes of TIDA neurons (i.e. GABAergic versus dopaminergic) of the arcuate nucleus and lactotroph-specific Prlr knockout in mice have revealed that the PRLR may have distinct physiological outputs in these different cell types (16,26). Thus, the Akt pathway may mediate PRL-specific responses in one cell type, while having no function or a different function in another cell type and the local expression of different PRLR isoforms may also impact on whether Akt signaling is activated by the PRLR (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, deletion of Prlr in different subtypes of TIDA neurons (i.e. GABAergic versus dopaminergic) of the arcuate nucleus and lactotroph-specific Prlr knockout in mice have revealed that the PRLR may have distinct physiological outputs in these different cell types (16,26). Thus, the Akt pathway may mediate PRL-specific responses in one cell type, while having no function or a different function in another cell type and the local expression of different PRLR isoforms may also impact on whether Akt signaling is activated by the PRLR (9).…”
Section: Discussionmentioning
confidence: 99%
“…Support for this mechanism is provided by studies of mice lacking the dopamine D2 receptor, which are hyperprolactinaemic due to loss of dopaminergic inhibition at the pituitary gland (15). Interestingly, PRLR has also been reported to be expressed on lactotrophs of the pituitary gland where it may provide an autocrine loop to regulate lactotroph function (16). Moreover, human and rodent studies have reported roles for the PRLR in reproduction and development of breast and prostate tumors (17–19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRL secretion is mainly under inhibitory stimuli, via tuberoinfundibular dopamine (TIDA) neurons in the hypothalamus binding to Type 2 Dopamine Receptor (D2R) and GABA (gamma aminobutyric acid), the latter playing a minor role [21]. PRL also controls its own secretion through a short loop negative feedback, stimulating TIDA cells [22] and in the own lactotroph cell by an autocrine loop [23] (Figure 2). There are also prolactinreleasing factors (PRFs) such as thyrotropin-releasing hormone, vasoactive intestinal peptide, serotonin, histamine, oxytocin and oestrogens [24].…”
Section: Prolactin Axismentioning
confidence: 99%
“…PRLR is expressed on TIDA cells (a short-loop feedback circuit) and also on lactotrophs of the pituitary gland where it may provide an autocrine loop to regulate lactotroph function [23]. The PRLR is a member of the cytokine receptor superfamily that signals via Janus kinase-2-signal transducer and activator of transcription-5 (JAK2-STAT5), phosphoinositide 3-kinase-Akt (PI3K-Akt-mTOR) or the MAPK pathways to mediate changes in transcription, differentiation and proliferation [36] (Figure 3).…”
Section: Prolactin Receptor Intracellular Signalling and Autocrine Functionmentioning
confidence: 99%